2023
DOI: 10.1021/acscatal.3c02468
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Olefin Cyclopropanation with In Situ-Generated Dialkyl Diazomethanes via Co(II)-Based Metalloradical Catalysis

Bao-Gui Cai,
Claire Empel,
Sripati Jana
et al.

Abstract: The synthesis of dialkyl-substituted cyclopropanes is an important challenge in synthesis with applications in drug discovery and agrochemistry. Herein, we report on the synthesis of gem-dialkyl cyclopropanes with in situ-generated dialkyl diazo compounds under Bamford−Stevens conditions. A simple cobalt catalyst was identified to be optimal to achieve high yields. Experimental and computational studies suggest the participation of a metalloradical reaction mechanism that facilitates the carbene transfer react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…2, which implies that O 2 would not be activated. 12 The EPR signal that the alkyl radical trapped by TEMP verified that aldehydes could undergo decarbonylation easily under irradiation, which again confirmed that aldehydes act as excellent alkyl radical precursors in the photosystems. Then UV-Vis experiments were conducted.…”
Section: Resultsmentioning
confidence: 64%
“…2, which implies that O 2 would not be activated. 12 The EPR signal that the alkyl radical trapped by TEMP verified that aldehydes could undergo decarbonylation easily under irradiation, which again confirmed that aldehydes act as excellent alkyl radical precursors in the photosystems. Then UV-Vis experiments were conducted.…”
Section: Resultsmentioning
confidence: 64%
“…A steric focused investigation revealed disubstituted alkenes are also well-tolerated. For example, 1,1-disubstituted styrenes (11), simple alkenes (12), or allyl silanes (13), were all viable. Additionally, exocyclic methylenes provide rapid access to medicinally privileged spirocycles that fuse cyclopropanes with carbocycles (14), heterocycles (15), or small rings (16).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“… Yet, since carbene precursors often require stabilizing groups to prevent spontaneous decomposition, lengthy synthetic sequences are frequently needed to remove these vestiges. Recent advances by the laboratories of Uyeda ( gem- dihalides), Wilkerson-Hill (sulfones), and Koenigs/Xuan (hydrazones) now allow gem- dimethyl incorporation into cyclopropanes. However, a general solution to harness other diverse classes of nonstabilized alkyl carbenes–and avoid typical β-elimination byproducts , – remains desirable.…”
Section: Introductionmentioning
confidence: 99%
“…In one recent example, Zhang demonstrated asymmetric cyclopropanation reactions with trifluoromethylcarbenes using a cobalt metalloradical catalyst. [11,12] Related strategies include the oxidation of parent hydrazones [13] or conversions of primary amines to diazo compounds using NaNO 2 . [14] N-Sulfonyl triazoles or 1,2,3triazine 1-oxides may also be viewed as masked diazoalkanes via ring-opening processes.…”
Section: Redox Neutral Precursors For Substituted Carbenesmentioning
confidence: 99%